Foutenanalyses volgens globale of fijnmazige categorieën. Wat is de beste methode om spellingvaardigheid en ‒ontwikkeling in kaart te brengen?*: Een onderzoek naar hoe gedetailleerd de categorieverdeling moet zijn om de spellingvaardigheid en ‒ontwikkeling te beschrijven, geïllustreerd aan de hand van medeklinkerverdubbeling. - Eskes, Carine (Acta Neerlandica, 2015)
What is the best method to map out spelling competence and development? That question will be answered by means of consonant duplication at the primary school in grades 3 to 8 (Dutch system). According to previous research, describing spelling competence on the basis of global category 4.2 (‘inheemse verdubbelingswoorden’) in the Van Dale Basisspellinggids does not give enough information. Spelling development, on the other hand, seems to be described quite well with this global distinction as regardless of the possible differences in development of the ‘inheemse verdubbelingswoorden’, the ‘goedpercentage’ in the 8th grade almost reaches 100%. The more detailed breakdown in subcategories 4.2a, 4.2b, 4.2c and 4.2d show that ‘puddingwords’ (subcategory 4.2c: words ending in -ing, -ig, -lijk, a schwa that is not written as ) and ‘herrie-words’ (subcategory 4.2d: native ‘verdubbelingswoorden’ that look like other categories, but differ from them because they have more than one ‘volle vocaal’) hardly occur in the corpus. The ‘tamme words’ (subcategory 4.2a: words with a suffix which contain a schwa, written as ) and ‘korrel words’ (subcategory 4.2b: words ending in ‒el, -er which are part of the base, no flectional suffixes, schwa written as ) give a valuable description of the spelling competence and development. The detailed 38 Carine Eskes distinction in triplet clusters gives a clear picture and that is mainly because of the limited number of observations made in these categories